The Influence Of Training And Corporate Culture On Employee Performance - Budi Rismayadi; Wike Pertiwi (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — The purpose of this study is how the influence of Corporate Culture and Training on employee performance.. Research method— The method in this study is a quantitative descriptive method using multiple linear regression analysis. The research data comes from primary data and data collection process with a sample size of 50 people. Result— The results of this study indicate that there is a partial influence between corporate culture on performance significantly of 0.000 <0.005 and a t-count value of 7.584> 2.011 and a partial influence between training on performance significantly of 0.000 <0.005 and a t-count value of 3.793> 2.011. Together, corporate culture and training are proven to have a simultaneous significant influence on employee performance which shows a very significant influence of 0.000 <0.005 with an F-Count value of 186.501> 3.19. Based on the results of the determination coefficient, it was found that the variables of corporate culture and training had an influence of 88.8% while the remaining 1.2% was explained by other unknown factors or variables that were not included in this regression analysis such as work discipline, work environment. Conclusion— Partially, Corporate Culture Variable (X1) has a positive and very significant influence on Employee Performance variable (Y) in Karawang MSMEs. Partially, Training Variable (X2) has a positive influence on employee performance variable (Y), which means that training variable has an influence on employee performance in Karawang MSMEs. Simultaneously, Corporate Culture Variable (X1) and Training variable (X2) have a positive and significant influence on employee performance variable (Y) in Karawang MSMEs. effectiveness. Fourth, joint testing shows that Engagement, Work Supervision and Compensation simultaneously have a positive and significant effect on employee performance. This means that H0 is rejected and H4 is accepted so that it can be stated that the independent or independent variable (X) has a significant effect simultaneously or together on the dependent or dependent variable (Y).